Environmental noise exposure at kernel crush point / Satwinder Singh Narangan Singh - Satwinder Singh, Narangan Singh (2021)
In nearly every industry on the globe, noise pollution is a major problem. This article is a study of noise exposure at Kernel Crush Point's production area. The study's major goal is to determine noise exposure, compare noise levels to regulatory requirements, and compare current and previous noise levels (2016 and 2019). The methodologies utilized in this study were the Statistical Package for the Social Sciences (SPSS) Version 23.0. According to the findings, there was an excessive amount of noise present, which was usually over the action level as compared to the legal standard. There was no correlation between noise levels and machine line. There was a substantial variation in noise levels between recent and previous years (2016 and 2019). The proposal should be based on the hierarchy of control, which has been approved by many health and safety organizations. The five major components of the hierarchy of control are elimination, substitution, engineering control, administrative control, and personal protective equipment. Management should offer improved personal protective equipment (PPE) with a greater noise reduction rating (NRR) to reduce sound exposure in the workplace.